OBESITY IN THE FAMILY AS THE ETIOLOGICAL FACTOR IN OCCURRENCE OF HIGH BODY MASS AMONG CHILDREN AND THE ASSOCIJATED PSYCHOSOCIAL IMPLICATIONS - Dragan Krivokapić; Olivera Krivokapić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2009)
This research was inspired by the recently published results of the examination of public health in Montenegro conducted by Ministry of Health, Labor and Social Welfare of Montenegro in cooperation with the Institute of Public Health which were supported by the World Bank. The published results indicate that, among other things, more than a half of adult population and about 20 percent of children are overweight. Physical inac- tivity is stated to be the principal cause of it. Having in mind that the physical inactivity acts as the health risk factor upon which we can act preventively by the organized physi- cal activity, we conducted a research on incidence of obesity among elementary school children and their parents in order to identify possible correlation and, if possible, to reduce its occurrence. The results obtained show that there is a significant correlation between obesity among children and obesity among their parents. With the adequate education it would be possible to include families with this problem in well organized physical activities in order to reduce this omnipresent health problem.